Baccharis Dracunculifolia : avaliação química e formulação com ação fotoprotetora e antioxidante. - Isis Tavares Vilas Boas (2021)
Baccharis dracunculifolia is a plant native to Brazil, traditionally used by the population in the form of tea to treat inflammatory conditions. This indication for use is confirmed by studies on its chemical composition and pharmacological activities, including skin pathologies. Thus, the objective of this study was to evaluate the photoprotective and antioxidant action of the species B. dracunculifolia, using in vitro and in silico methods, correlating them with its phytochemical profile. For this, the extraction conditions of the plant material were studied to obtain extracts rich in phenolic substances and their chemical composition was verified by chromatographic analysis and mass spectrometry. The optimized ethanolic extract of B. dracunculifolia was evaluated for (i) antioxidant potential by scavenging the free radical 1,1-diphenyl-2-picrylhydrazyl; (ii) autoxidation of linoleic acid; (iii) in vitro sun protection factor (SPF); and (iv) evaluation of the antimutagenic potential in a yeast model. Finally, the stereoelectronic properties involved with the antioxidant action and UV absorption were studied in silico. It was possible to conclude that the use of ethanol solvent associated with reflux at 70 ºC as an extractive method allowed the extraction, mainly, of flavonoids and caffeoylquinic derivatives, artepilin C and prenylated derivatives. In synergy, these substances allowed greater antioxidant action, with effective concentration (EC50) equal to 12.9, and SPF 18.9 in vitro, responsible for broad-spectrum UV protection and antioxidant activity, observed in all experiments carried out. In in silico studies, the best electron donating capacity was observed in the flavonoid quercetin, while the highest antioxidant capacity was observed in chlorogenic acid. The in vitro analysis of the optimized extract in a model of Saccharomyces cerevisiae strains allowed confirmation of the potential for protection against cytotoxic and mutagenic lesions induced by UV radiation. The results obtained provide perspectives for more detailed investigations of the photoprotective and antioxidant effect of B. dracunculifolia and its quantitative standardization, aiming at its future use in photoprotective cosmetic formulations.